Stress and strain state of road slabs during production and use in the Western Siberia conditions - V.V. Babkov; R.A. Yumagulov; R.S. Kildibaev (Инженерно-строительный журнал, 2015)
Precast concrete road slabs are used for auto-road construction in the severe hydrogeologic and climatic conditions of Western Siberia. The advantages of precast concrete road pavements have been proved by more than half a century of use, which is confirmed by the current steady demand for this type of product. The problem of developing the precast concrete road system in the Western Siberian and the Far North regions is therefore still a critical task. The long experience of manufacturing and using prestressed concrete road slabs showed that they are at risk of crack formation not only when the road pavement is used but also at the manufacturing stage. To explore the reason of crack formation, stress and strain state analysis of road slabs was performed using the ANSYS 14.0 software. It was revealed that the existing prestressed reinforcement layout of the functional standard series enables the development of transverse tensile stress σty in slab ends and adjoining parts. The occurring tensile stress can initiate longitudinal cracks in operation by multiple repeated exposure typical for the road slab usage conditions. Based on the results of the analysis, a technical solution optimizing road slab reinforcement was suggested to reduce the detrimental effect of tensile stress in slab ends from the prestressing force. The optimization involves increasing the distribution dispersability of tensile reinforcement at cross-sections by the prestressing force without sacrificing its prestress capacity, resulting in reducing tensile transverse stress to acceptable levels.